Analysis of the pseudogap-related structure in tunnel spectra of the superconducting Bi2Sr2CaCu2O8+d revealed by break-junction technique - Ekino, T.; Gabovich, A.M.; Voitenko, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Tunnel conductance G(V)for break-junctions made of as-grown single-crystal Bi2Sr2CaCu2O8+d sampleswith Tc ≈ 86-89 K was measured and clear-cut dip-hump structures (DHSs) were found in the range80 - 120mV of the bias voltage V. The theory of tunneling in symmetric junctions between inhomogeneous charge-density-wave (CDW) superconductors, considered in the framework of the s-pairing model, has been developed. CDWs have been shown to be responsible for the appearance of the DHS in the tunnel current-voltage characteristics and properly describes experimental results.